THE PERCEPTIONS OF FOURTH SEMESTER ENGLISH STUDENTS ON LISTENING COMPREHENSION STRATEGIES AND LISTENING SKILL - Muzzayanatus Solihah Muklas (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2019)
ABSTRACTThis study aims to find out difference effects among higher score students’ perceptions and lower score students’ perceptions towards their listening comprehension strategies and listening skill of Fourth Semester English Students of UNISMA and also the influence of their perceptions. The research design in the present study is quantitative research in the form of expo facto design. 60 students samples were taken by random sampling technique. The data were collected by using middle test scores for grouping the students and questionnaire for representations of their perceptions. The data were analyzed by using quantitative techniques in IBM SPSS Statistic 20.0 Program. Deeply, the questionnaires results were changed into quantitative data which were statistic data and percentage data. The findings were, first, both of the two groups are in moderate perception and, second, the students had given the same aggrement, deeply, almost 62% students in one idea on the influence of their perceptions that perception takes crucial influence in their listening comprehension strategies, listening input and achievements, students’ motivations and evaluation study, students’ learning independency, then the last on, listening skill. To sum up, students need to find their perception of learning listening skill in order to support mastering their three upcoming English skills.